2012
DOI: 10.1186/2008-2231-20-39
|View full text |Cite
|
Sign up to set email alerts
|

The effect of Camellia Sinensis (green tea) mouthwash on plaque-induced gingivitis: a single-blinded randomized controlled clinical trial

Abstract: Background and the purpose of the StudyComplementary medicine received high attention during last decades. We aimed to assess the efficacy of Green tea mouthwash on plaque-induced gingivitis as the most common form of periodontal disease.Methods and materialsWe designed a single blinded placebo controlled clinical trial. High school female students with chronic generalized plaque-induced gingivitis were distributed to receive either 5 ml of Green tea 5% two times/day or normal saline with the same dosage. Ging… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
33
0
7

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(49 citation statements)
references
References 18 publications
3
33
0
7
Order By: Relevance
“…Catechins of green tea (EGC, EGCg, and ECg) possess antibacterial activities and in vitro and in vivo studies have reported effectiveness of green tea against bacteria in periodontal diseases and caries [1,16]. Hence, the results of the current study could be also attributed to antibacterial properties of green tea mouthwash along with its anti-inflammatory activity.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Catechins of green tea (EGC, EGCg, and ECg) possess antibacterial activities and in vitro and in vivo studies have reported effectiveness of green tea against bacteria in periodontal diseases and caries [1,16]. Hence, the results of the current study could be also attributed to antibacterial properties of green tea mouthwash along with its anti-inflammatory activity.…”
Section: Discussionmentioning
confidence: 56%
“…Green tea is very rich in polyphenols including catechins which possess antioxidant, antidiabetic, antimutagenic, antiviral, antibacterial, and anti-inflammatory properties [15]. It has reported that green tea is effective on periodontal diseases and is also beneficial against cariogenic activities [16-19]. However, there exists no study to investigate benefits of green tea extract in controlling postoperative complications in oral surgeries.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it is thought that antioxidants may be beneficial in treating inflammatory diseases. Moreover, the systemic action of catechins seems to contribute to a decrease in the activity of proteinases 20 and a decrease in osteoclast formation 21 , thereby interfering with the normal course of periodontal diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Our results corroborate evidence demonstrating in vitro antimicrobial activity of green tea on various bacteria 15,16 . Furthermore, the consumption of green tea can provide clinical benefits in the treatment of gingivitis 13,20 and periodontitis with greater reductions in probing depth and gains in clinical attachment 9 . It is possible that this systemic effect is due to the powerful antioxidant effects of green tea, as it is known that oxidative stress plays an important role in the pathogenesis of periodontal diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Devido à sua comprovada eficácia contra os micro-organismos e na inibição de metaloproteinases, esse extrato tem sido incorporado em materiais odontológicos, tais como, adesivos dentinários (Du et al, 2012), resinas compostas Mankovskaia et al, 2013) e cimentos de ionômero de vidro (Hu et al, 2013). Além disso, seu uso tem sido sugerido na redução da erosão e abrasão dentária (Magalhães et al, 2009;Kato et al, 2010), em solução para bochechos (Hirasawa et al, 2006;Jenabian et al, 2012;Neturi et al, 2014;Sarin et al, 2015), em dentifrícios (Maruyama et al, 2011;Hrishi et al, 2015) e como meio para a conservação de dentes avulsionados após traumatismos, mantendo a vitalidade das células do ligamento periodontal (Hwang et al, 2011;Jung et al, 2011;Poi et al, 2013;Ghasempour et al, 2015).…”
Section: Introductionunclassified